The impact of the Health Silk Road on Global South countries: insights from Brazilian health agents - Santiago, Anabela Rodrigues; Rodrigues, Carlos (Frontiers in Political Science, 2023)
China is currently ranked second in the world economy, and its political role in the global order has increased in recent decades. As part of one of its modern and emblematic international projects, the Belt and Road Initiative (BRI) is the Health Silk Road, which can be considered a branch officially launched in 2017. Driven by some external factors, the most important of which is the COVID-19 pandemic, the Health Silk Road and Chinese public health policies have gained accrued relevance, especially in countries of the Global South, which have been the main partners of Chinese cooperation initiatives, not only in health. This study is an exploratory exercise that reflects the potential gains resulting from Chinese-Global South cooperation in the health sector by analyzing the perceptions of Brazilian health agents in a contemporary period going from 2013 until 2023 for being the first 10 years since BRI implementation. We intended to answer the following questions: Does Brazil benefit from health partnerships with China, specifically under the Health Silk Road, despite not having formally joined the BRI? What are the privileged health areas of implementation and what are the gains? These questions were answered through interviews with Brazilian researchers from public institutions to obtain their perspectives and insights regarding the practical aspects of partnerships.